Marketing Activities to Support 'Moderately Novel' Product Innovation: Insights from the Chemical Industry. (7th May 2015) - Smits, Armand; Vissers, Geert; Dankbaar, Ben
<x xml:space="preserve">Abstract</x> Scholars often follow a contingency approach to study which marketing activities are suitable for a particular type of product innovation project, thereby making a distinction between incremental and radical innovation only. 'Moderately novel' projects, which have intermediate levels of newness, have therefore not been given due attention. This paper focuses on market intelligence generation and the creation of cross‐functional linkages as marketing activities that are important in the context of moderately novel product innovation. In addition, the organizational position of the marketers involved in these activities is dealt with. Based on the analysis of four successful projects in the chemical industry, we argue, firstly, that moderately novel innovation projects have their own particular sets of marketing practices and, secondly, that differences exist between projects aiming at a new market segment and projects in which novelty is not related to market segment but to other market dimensions. These differences are especially salient in early project phases. These findings are pertinent to research on the role of marketers in product innovation, and to the study of organizational ambidexterity.